2020
DOI: 10.1210/clinem/dgaa808
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density and Turnover After Sleeve Gastrectomy and Gastric Bypass: A Randomized Controlled Trial (Oseberg)

Abstract: Context Bariatric surgery, particularly Roux-en-Y gastric bypass (RYGB), is associated with increased risk of osteoporotic fractures. It is unknown whether RYGB or sleeve gastrectomy (SG) have different effects on bone health. Objective To compare changes in bone mineral density and markers of bone turnover one year after SG and RYGB. Design, Setting, Patients, and Interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…At the hip, BMD loss was significantly higher in patients undergoing SG (-9.2%) and RYGB (-9.5%) than intensive medical therapy group (-0.3%), whereas at lumbar spine a significant decrease in BMD was only observed in the SG group (-2.3%), without changes in RYGB (0.4%) and intensive medical therapy groups (0.8%). A subsequent randomized controlled trial in patients with obesity and T2DM demonstrated that subjects undergoing RYGB had a higher decrease in BMD at the femoral neck (mean between-group difference -2.8%, 95% CI -4.7 to -0.8), total hip (mean betweengroup difference -3.0%, 95% CI -5.0 to -0.9) and lumbar spine (mean between-group difference -4.2%, 95% CI -6.4 to -2.1) than patients undergoing SG (45).…”
Section: Bone Mineral Density After Bariatric Surgerymentioning
confidence: 92%
See 2 more Smart Citations
“…At the hip, BMD loss was significantly higher in patients undergoing SG (-9.2%) and RYGB (-9.5%) than intensive medical therapy group (-0.3%), whereas at lumbar spine a significant decrease in BMD was only observed in the SG group (-2.3%), without changes in RYGB (0.4%) and intensive medical therapy groups (0.8%). A subsequent randomized controlled trial in patients with obesity and T2DM demonstrated that subjects undergoing RYGB had a higher decrease in BMD at the femoral neck (mean between-group difference -2.8%, 95% CI -4.7 to -0.8), total hip (mean betweengroup difference -3.0%, 95% CI -5.0 to -0.9) and lumbar spine (mean between-group difference -4.2%, 95% CI -6.4 to -2.1) than patients undergoing SG (45).…”
Section: Bone Mineral Density After Bariatric Surgerymentioning
confidence: 92%
“…Comparative analyses between RYBP and SG showed a significantly higher increase in CTX, P1NP, TRAcP5b with the former, and a greater increase in total OC and uOC with the latter, suggesting a predominating bone resorption over bone formation markers during RYGB ( 36 ). A randomized triple-blind trial showed an approximately 100% higher increase in P1NP and CTX-1 levels after RYGB than SG at 1-year post surgery ( 45 ). Likewise, studies after biliopancreatic diversion (BPD) showed that CTX increased significantly at 3 days (+ 66%), 3 months (+ 219%), and 12 months (+ 295%), while OC decreased at 3 days (- 19%) then increased at 3 months (+ 69%) and 12 months (+ 164%), suggesting an earlier and greater increase in bone resorption over bone formation markers with BPD ( 120 ).…”
Section: Bone Turnover Markers After Bariatric Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the use of zoledronic acid is a strength because a single dose has been shown to suppress bone turnover in various disease states (osteoporosis, 30 Paget’s disease, 31 HIV 32 and androgen deprivation therapy 33 ) for between 12 months and 6.5 years. 11 Considering SG results in increased bone turnover for anywhere between 1 and 5 years following surgery, 34 35 zoledronic acid, with its robust bone turnover suppression, is an ideal treatment option in this population to combat skeletal fragility.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there is accumulated evidence demonstrating a reduction in bone mineral density (BMD) [9,10] after a bariatric procedure. Studies that compared the two most commonly performed techniques [11] showed significantly more bone loss after Rouxen-Y gastric bypass (RYGB) than after sleeve gastrectomy (SG), especially in the lumbar spine, total hip, and femoral neck [9,10]. This undesired event may result in greater skeletal frailty and risk of fractures [12,13].…”
Section: Introductionmentioning
confidence: 99%